O05.2 Characterizing the impact of penile-vaginal sex on HIV-susceptible CD4+ T cell subsets in the female genital tract. (14th July 2019) - Mohammadi, Avid; Bagherichimeh, Sareh; Fazel, Azadeh; Tevlin, Elizabeth; Tharao, Wangari; Kaul, Rupert
Abstract : Background: HIV in women is often acquired across the female genital tract mucosa, and a key parameter determining mucosal HIV susceptibility is the density of HIV-susceptible CD4+ T cells, particularly activated CD4+ T cells and Th17 cells. However, although most HIV transmission occurs during sex, the impact of sex itself on CD4+ T cell subsets is poorly described. Methods: STI-free heterosexual couples (N=40) were recruited. Blood, cervicovaginal secretions and a cervical cytobrush were collected from the female partner at baseline; couples then had penile-vaginal sex 48h later, with repeat sampling after 1–2 hr and 72 hr. Couples either had unprotected sex (n=31) or condom-protected sex (n=11); two couples participated twice, once with and once without a condom. Cytobrush-derived CD4+ T cell subsets were assessed by flow cytometry, and paired changes assessed by Wilcoxon signed-rank test. Results: The proportion of endocervical Th17 (CCR6+) cells transiently increased 1–2 hr after penile-vaginal sex (median increase = 4.95%; p=0.006), and returned to baseline by 3 days. Endocervical activated (HLA-DR+) CD4+ T cells also increased after 1–2 hr, but these increases persisted for >72 hr (1.63%; p= 0.007 and 4.75%; p< 0.0001, respectively). Importantly, increases in both types of HIV target cells were only apparent after condomless sex (5.0% for CCR6; P=0.015 and 2.11% for HLA-DR; p=0.006), with no increase seen after condom-protected sex (1.1% for CCR6; 0.7% for HLA-DR; both p>0.3). The expression of CCR5 and the frequency of other cervical CD4+ T cell subsets, including Th1 and Trm, were unchanged after sex. Conclusion: Penile-vaginal sex rapidly increased the proportion of cervical Th17 cells and activated CD4+ T cells, thought to be key endocervical CD4+ T cell HIV targets. Future work will assess the impact of sex on genital cytokine levels and the microbiota, and correlate cervical immune changes with semen parameters in the male partner. Disclosure: No significant relationships.